Antiphotoaging effect of boiled abalone residual peptide ATPGDEG on UVB-induced keratinocyte HaCaT cells - Jiali Chen (Food & Nutrition Research, 2019)
Introduction: A previous study has shown that Ala–Thr–Pro–Gly–Asp–Glu–Gly (ATPGDEG) peptide identified from boiled abalone by-products has high antioxidant activities and antihypertensive effect. Objective: In this study, we further investigated its antiphotoaging activities by ultraviolet B (UVB)-induced HaCaT cells. Result: UVB irradiation significantly increased the content of intercellular reactive oxygen species (ROS) and the production of matrix metalloproteinases (MMPs) in HaCaT cells and decreased its content of collagen. First, the generation of intercellular ROS was reduced by abalone peptide in UVB-induced HaCaT cells. And activities of MMP-1 and MMP-9 were reduced by abalone peptide in a dose-dependent manner. Furthermore, western blot analysis demonstrated that abalone peptide downregulated the expression of p38, c-Jun N-terminal kinases, and extracellular signal-regulated kinases via mitogen-activated protein kinases (MAPKs) and NF-κB signaling to protect type I pro collagen and DNA damage. Molecular docking simulation confirms that abalone peptide inhibited activities of MMP-1 and MMP-9 by docking their active site, among them N-terminal Ala, C-terminal Gly, and Pro at the third position of N-terminal made a great contribution. Conclusion and recommendation: Abalone peptide could protect type I procollagen synthesis in UVB-irradiated HaCaT cells, and it is a potential peptide for the treatment of skin photoaging in the future.